نمذجة الفرن الشمسي واختباره - صبيح, مسعود (Latakia University Journal -Engineering Sciences Series, 2019)
سندرس في هذا البحث نموذج الفرن الشمسي (Sun Oven) من أجل الحصول على التسخين الحراري المطلوب لمحتويات وعاء الطهي للفرن الشمسي. إن إضافة مواصفات تصميمية ممثلة باستخدام عدسات أو عواكس للأشعة الشمسية، وإسقاطها مباشرة على قاعدة الفرن الشمسي، أثرت على نحو مباشر على نتائج العمل والأداء وأسهمت في زيادة المردود الحراري للفرن الشمسي. إن هذه الدراسة يمكن تصنيفها في دراسة نظرية تحليلية ودراسة عملية تطبيقية. الدراسة النظرية تمثلت بإعداد النمذجة الرياضية لكل أجزاء ومكونات الفرن الشمسي، من خلال استخدام معاملات الانتقال الحراري الى داخل الفرن الشمسي كقدرة حرارية مكتسبة وإلى الوسط الخارجي كمفاقيد أو ضياعات. الدراسة العملية أو التطبيقية أتت من خلال الإجراء التجريبي للفرن الشمسي في بلدة غباغب التابعة إلى محافظة درعا، والقيام برصد ومراقبة السلوك الحراري للفرن الشمسي وتسجيل بيانات الحرارة المكتسبة مع الزمن. إجراء المقارنة بين الدراسة النظرية والإجراء التطبيقي واستنتاج التوصيات المفيدة للعمل المستقبلي. We study in this research a model of sun oven to obtain thermal heating required for the contents of a cooking pot for sun oven. Adding designative specification represented by the usage of lens and reflectors of solar radiation and projecting it directly on the base of sun oven had affected directly the results of work and performance and contributed to increasing the thermal efficiency of the sun oven. This study is both theoretical analytical. The theoretical part is represented in the preparation of mathematical modeling of all parts and components of the sun oven by usage of thermal transmission coefficients into the sun oven as a gained thermal power and to the external media as losses and wastes. The practical or applied part is represented in the experimental procedure of the sun oven in Ghabagheb town of Daraa Governorate and in the control and supervision of thermal temperature of sun oven and registry of statements of gained temperature through time. The paper ends with a comparison between the theoretical study and applied procedure as well as a conclusion of a useful recommendation for future work.